Effect of Extreme ENSO and IOD on the Variability of Chlorophyll-a and Sea Surface Temperature in the North and South of Central Java Province - Kunarso Kunarso; Dwi Haryo Ismunarti; Azis Rifai; Bayu Munandar; Anindya Wirasatriya; Raden Dwi Susanto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Chlorophyll-a (chl-a) and Sea Surface Temperature (SST) are important indicators of air-sea interaction and primary productivity. It has been widely known that the variability of chl-a and SST in the waters of Central Java Province (CJP) is influenced by the monsoonal cycle. Previous studies did not clearly describe the variability of chl-a and SST when compared to other cycles. This present study investigated the variability of chl-a and SST influenced by monsoonal cycles, IOD, and ENSO in both CJP waters. Our analysis is based on satellite observations and uses daily data to compile climatological data. The analysis found differences between the variability of chl-a and SST during the monsoonal cycle and ENSO-IOD extreme conditions. During the monsoonal cycle, the maximum (minimum) chl-a (SST) in northern CJP is 0.7 mg.L-1 (28.5ºC) is observed in the West Monsoon, and in the southern CJP is 1.5 mg.L-1 (25.5ºC) is observed in the East Monsoon. In addition, the analysis reveals that the ENSO and IOD extremes do not clearly alter the variability of chl-a and SST in the northern CJP. However, ENSO and IOD extremes have clearly altered the variability of chl-a and SST in the southern CJP. The highest impact to variability of chl-a and SST occurred during IOD+ extreme (2019), where the range of value chl-a (SST) in south CJP is 0,35–4,57 mg.L-1 (23,29 – 30,49ºC). The value of chl-a (SST) is greater than 4 mg.L-1 (less than 24ºC) are observed in the east monsoon. It is caused by the intensity of lifting the mass of water from deeper waters to the sea surface, which possibly supplies the nutrients in the surface waters. The result of the investigation showed that the increasing of chl-a and decreasing of SST in the northern CJP dominant by monsoonal cycle and southern CJP dominant by monsoonal cycle and ENSO – IOD.